Behavioral assessment of Tambaqui juveniles (Colossoma macropomum) exposed to different ambient colors and social stress (Bioscience Journal, 2023)
Animal welfare regards the quality of life and the environment in which animals live or are exposed. Hence the importance of studies assessing the environmental influence on the biology and behavior of fishes from the Colossoma macropomum species, considering their higher potential for fish-farming and as a test organism in scientific research. This study aimed to assess, in a controlled environment, the behavioral changes expressed by juveniles from the Colossoma macropomum species exposed to different ambient colors or social situations. The results did not show an influence from the different ambient colors or social situations on fish distribution in the water column. The color pattern showed dark tones in black- and blue-colored environments, and light tones in white-colored environments or with the presence of a mirror. The time of locomotor activity/frequency did not change in any of the treatments of exposure to environments with colors and a mirror. Moreover, the fishes remained with folded fins and a straight posture, maintaining a pattern of rhythmic operculum beating in a normal frequency range described for the species. This suggests that animal welfare did not change in any of the situations tested and that there was a pattern of adaptive response to the type of environment.